2016
DOI: 10.3389/fpsyg.2016.00403
|View full text |Cite
|
Sign up to set email alerts
|

Dependency Resolution Difficulty Increases with Distance in Persian Separable Complex Predicates: Evidence for Expectation and Memory-Based Accounts

Abstract: Delaying the appearance of a verb in a noun-verb dependency tends to increase processing difficulty at the verb; one explanation for this locality effect is decay and/or interference of the noun in working memory. Surprisal, an expectation-based account, predicts that delaying the appearance of a verb either renders it no more predictable or more predictable, leading respectively to a prediction of no effect of distance or a facilitation. Recently, Husain et al. (2014) suggested that when the exact identity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 38 publications
2
34
1
Order By: Relevance
“…Some other important future directions in modeling comprehension impairments in aphasia are the following: (a) Expand the cross-linguistic empirical base of the investigation. Previous work [44] has relied on the available data from English, but large-sample data-sets from other languages are needed: the diversity of grammatical constraints, word orders, and morphosyntactic cues available in different languages are known to lead to different processing strategies even in unimpaired populations [63,64,65,66], and such factors may play a role in aphasia as well [67,68]. (b) Evaluate the relative predictive performance of different (retrieval) theories using data from individuals with aphasia and controls.…”
Section: Modeling and Understanding Impairments In Sentence Comprehenmentioning
confidence: 99%
“…Some other important future directions in modeling comprehension impairments in aphasia are the following: (a) Expand the cross-linguistic empirical base of the investigation. Previous work [44] has relied on the available data from English, but large-sample data-sets from other languages are needed: the diversity of grammatical constraints, word orders, and morphosyntactic cues available in different languages are known to lead to different processing strategies even in unimpaired populations [63,64,65,66], and such factors may play a role in aphasia as well [67,68]. (b) Evaluate the relative predictive performance of different (retrieval) theories using data from individuals with aphasia and controls.…”
Section: Modeling and Understanding Impairments In Sentence Comprehenmentioning
confidence: 99%
“…In particular, it has been claimed that head‐final languages (e.g., German, Hindi, Japanese) allow for longer head‐dependent distance. Previous work on predictive processing (Husain et al, 2014; Konieczny, 2000; Levy & Keller, 2013; Miyamoto & Nakamura, 2003; Nakatani & Gibson, 2010; Vasishth & Lewis, 2006) as well as the forgetting effect (Frank & Ernst, 2019; Frank et al, 2016; Husain & Bhatia, 2018; Vasishth et al, 2010) shows that head‐final languages allow for longer distance in dependencies involving verbal heads (but see Safavi, Husain, & Vasishth, 2016; Vasishth & Drenhaus, 2011). For example, with regard to the forgetting effect, it has been shown that contrary to the results in an SVO language like English, in SOV languages like German, Dutch, and Hindi, increased HD (in the form of embedding) does not lead to forgetting of the upcoming verbs.…”
Section: Discussionmentioning
confidence: 99%
“…Such evidence against locality has been used to argue for the expectation‐based account of Levy (), a variant of the experience‐based theories. Recent work has also shown evidence for both locality effects and expectation effects in English (Demberg & Keller, ; Jaeger, Fedorenko, Hofmeister, & Gibson, ; Staub, 2010), German (Levy & Keller, ; Vasishth & Drenhaus, ), Hindi (Husain, Vasishth, & Srinivasan, , ), Persian (Safavi, Husain, & Vasishth, ), and Russian (Levy et al., ).…”
Section: Introductionmentioning
confidence: 98%